BETWEEN IDENTITIES AND LISTENING:: BETWEEN IDENTITIES AND LISTENING: PSYCHOLOGICAL CLINICAL PRACTICES IN CHILD AND ADOLESCENT MENTAL HEALTH OUTPATIENT CLINIC (PRÁXIS EM SAÚDE, 2025)
This article, based on a qualitative research through an experience report, proposes a reflection on the modes of subjectivation that emerge in contexts of vulnerability, drawing from an internship experience in a child and adolescent multidisciplinary outpatient clinic in the Agreste region of Pernambuco, Brazil. Through clinical follow-up, the discussion focuses on the construction of parallel identities as psychic survival strategies in the face of experiences marked by pain, exclusion, and violence. It is assumed that identity constitutes a dynamic, relational process, shaped by multiple determinations — social, historical, cultural, and affective. Within this context, Dissociative Identity Disorder (DID) is highlighted as a clinical manifestation that expresses the complexity of subjective crossings, understood not as an isolated pathology, but as an extreme psychic response to early trauma. The analysis seeks to shift the focus from pathologization to a sensitive and engaged clinical listening, recognizing dissociation as an attempt to preserve the subject’s existence in unbearable contexts. Thus, the article invites the appreciation of the power of subjective reinvention at the margins of pain, exclusion, and resistance.
Keywords: Subjectivation; Dissociative Identity Disorder; Clinical listening.; Vulnerability; Identity